Two Preputial Gland-Secreted Pheromones Evoke Sexually Dimorphic Neural Pathways in the Mouse Vomeronasal System - Liu, Qun; Zhang, Yaohua; Wang, Pan; Guo, Xiao; Wu, Yijun; Zhang, Jian-Xu; Huang, Liquan (Frontiers in Cellular Neuroscience, 2019)
Hexadecanol (16OH) and hexadecyl acetate (16Ac) are two pheromones secreted in a large quantity by mouse preputial glands and act on male and female mice differentially. Yet the underlying molecular and cellular mechanisms remain to be elucidated. In this study, we examined the activation of vomeronasal sensory neurons (VSNs) by these two pheromones and mapped the downstream neural circuits that process and relay their chemosignals. Using the calcium imaging method and immunohistochemistry, we found that a small number of VSNs were activated by 16OH, 16AC or both in the male and female mice, most of which were located apically in the vomeronasal epithelium, and their numbers did not increase when the concentrations of 16OH and 16Ac were raised by 10,000 fold except that of female VSNs in response to 16OH. In the accessory olfactory bulb (AOB), the two pheromones evoked more c-Fos+ neurons in the anterior AOB (aAOB) than in the posterior AOB (pAOB); and the increases in the number of c-Fos+ neurons in both aAOB and pAOB were dose-dependent; and between sexes, the female AOB responded more strongly to 16OH than to 16Ac whereas the male AOB had the opposite response pattern. This sexual dimorphism was largely retained in the downstream brain regions, including the bed nucleus of the stria terminalis (BNST), the medial amygdaloid nucleus (MeA), the posteromedial cortical amygdaloid nucleus (PMCo), the medial preoptic area (MPA) and the ventromedial hypothalamic nucleus (VmH). Taken together, out data indicate that there are one V1r receptor each for 16OH, 16Ac or both, and that activation of these receptors evokes sexually dimorphic neural circuits, directing different behavioral outputs and possibly modulating other pheromone-induced responses.